2006
DOI: 10.1007/s10763-006-9048-5
|View full text |Cite
|
Sign up to set email alerts
|

The Durability of Conceptual Change in Learning the Concept of Weight in the Case of a Pulley in Balance

Abstract: This study concerns the question of how teachers can help pupils to perceive the concept of weight (gravitation). Fifth and ninth graders were asked in a paper-and-pencil test to compare the weight of two objects suspended in a pulley-inbalance half a year after the learning intervention consisting of three successive pulleyin-balance demonstrations. The understanding, that some of the fifth graders seemed to have formed from the weight concept after the teacher-independent learning intervention, had almost to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Their survey with pre-service biology teachers revealed that students' conceptions about force and motion improve during the first and second years (of their program) as they take physics classes, and decline afterwards. Similarly, Hakkarainen & Ahtee (2007) reported that the correct understanding of weight concept that fifth graders gained as a result of an intervention study had almost vanished 6 months after the intervention.…”
Section: Results and Implicationsmentioning
confidence: 96%
“…Their survey with pre-service biology teachers revealed that students' conceptions about force and motion improve during the first and second years (of their program) as they take physics classes, and decline afterwards. Similarly, Hakkarainen & Ahtee (2007) reported that the correct understanding of weight concept that fifth graders gained as a result of an intervention study had almost vanished 6 months after the intervention.…”
Section: Results and Implicationsmentioning
confidence: 96%
“…This condition forces educational institutions, especially lecturers, to develop learning so that it can still be held optimally even though they have to go through online meetings to maintain the mission of responding to the challenges and needs of the Industrial Revolution 4.0 era, namely equipping students with critical thinking, communication, creative thinking, and collaboration skills, or known as 4C (Hakkarainen & Ahtee, 2007).…”
Section: Introductionmentioning
confidence: 99%